Quality assurance in the pathology laboratory : forensic, technical, and ethical aspects - Bogusz, Maciej J. (CRC Press, 2011)
Quality refers to the amount of the unpriced attributes contained in each unit of the priced attribute. Leffler, 1982 Quality is neither mind nor matter, but a third entity independent of the two, even though Quality cannot be defined, you know what it is. Pirsig, 2000 The continuous formulation of good practices and procedures across fields reflects the importance of the recognition and maintenance of "quality" for nearly every profession. The widespread introduction of point-of-care testing, centralization of activities in large core laboratories, and the increase in number and com.